Electrochemical Detection of Ultra-trace Cu(II) and Interaction Mechanism Analysis Between Amine-Groups Functionalized CoFe2O4/Reduced Graphene Oxide Composites and Metal Ion. (1st November 2016) - Xiong, Shiquan; Ye, Shoudong; Hu, Xianhai; Xie, Fazhi
Abstract: The polyethylenimine (PEI) or ethanediamine (EDA) has been employed to adsorb metal ions. However, both the combination of CoFe2 O4 -reduced graphene oxide (rGO) with PEI or EDA for the analysis of Cu(II) determination and interaction mechanism towards copper ion by electrochemical method and X-ray photoelectron spectroscopy (XPS) are, to the best of our knowledge, unexplored. The amine functionalized rGO/CoFe2 O4 composite were synthesized through a one-pot method, and characterized by electrochemical method and different spectra such as FT-IR, XRD, XPS, etc. The lowest detection limit with 20 pM (3δ method) and sensitivity with 0.39 μA/nM towards Cu(II) was obtained at PEI/rGO/CoFe2 O4 modified electrode under optimized condition. The characteristics of Cu(II) on the amine-group functionalized CoFe2 O4 /rGO composite were investigated by cyclic voltammetry and XPS. The shifts of O and N peaks of PEI (or EDA)/CoFe2 O4 /rGO preconcentrating Cu(II) showed the synergistic effect of CoFe2 O4 /rGO and PEI (or EDA) to Cu(II). The analysis indicated that the interaction between the composite and Cu(II) was adsorption control process. The proposed electrode was also employed to the analysis of real soil sample. Thus, the proposed method and interaction mechanism analysis based on adsorption interaction could provide a reference for further investigate the pollution of metal ions.